(untitled) (Proceedings of International Educators Conference, 2024)
Digital platforms are common in growth and the digital economy, facing a number of challenges and challenges that need to be addressed. Some major problems arose: 1) regulatory challenges: one of the biggest challenges facing digital platforms is the need to comply with a wide range of regulations and legal requirements. This can be especially difficult in countries where the rules are not clear or where there is a large difference between jurisdictions. Regulatory challenges refer to legal and policy issues that arise in relation to the growth and use of digital platforms in the economy. Due to the disruptive nature of digital platforms, the need for regulation to comply with technological progress, and the potential to negatively impact traditional industry and society, these challenges can arise. Examples of regulatory challenges include issues related to data privacy, intellectual property rights, taxation, and labor laws. Digital platforms may also have problems with competition and market concentration, as some platforms may dominate their respective markets and create barriers to entry for new entrants. These challenges require policymakers to balance between innovation and growth promotion while protecting the rights and interests of all stakeholders.)